Sex-specific differences in hepatic steatosis in obese spontaneously hypertensive (SHROB) rats - Dong, Qingming (Biol Sex Differ, 2018)
BACKGROUND: Patients with metabolic syndrome, who are characterized by co-existence of insulin resistance, hypertension, hyperlipidemia, and obesity, are also prone to develop non-alcoholic fatty liver disease (NAFLD). Although the prevalence and severity of NAFLD is significantly greater in men than women, the mechanisms by which gender modulates the pathogenesis of hepatic steatosis are poorly defined. The obese spontaneously hypertensive (SHROB) rats represent an attractive model of metabolic syndrome without overt type 2 diabetes. Although pathological manifestation caused by the absence of a functional leptin receptor has been extensively studied in SHROB rats, it is unknown whether these animals elicited sex-specific differences in the development of hepatic steatosis. METHODS: We compared hepatic pathology in male and female SHROB rats. Additionally, we examined key biochemical and molecular parameters of signaling pathways linked with hyperinsulinemia and hyperlipidemia. Finally, using methods of quantitative polymerase chain reaction (qPCR) and western blot analysis, we quantified expression of 45 genes related to lipid biosynthesis and metabolism in the livers of male and female SHROB rats. RESULTS: We show that all SHROB rats developed hepatic steatosis that was accompanied by enhanced expression of SREBP1, SREBP2, ACC1, and FASN proteins. The livers of male rats also elicited higher induction of Pparg, Ppara, Slc2a4, Atox1, Skp1, Angptl3, and Pnpla3 mRNAs. In contrast, the livers of female SHROB rats elicited constitutively higher levels of phosphorylated JNK and AMPK and enhanced expression of Cd36. CONCLUSION: Based on these data, we conclude that the severity of hepatic steatosis in male and female SHROB rats was mainly driven by increased de novo lipogenesis. Moreover, male and female SHROB rats also elicited differential severity of hepatic steatosis that was coupled with sex-specific differences in fatty acid transport and esterification. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13293-018-0202-x) contains supplementary material, which is available to authorized users.